Does PPP hold between Asian and Japanese economies? Evidence using panel unit root and panel cointegration - Mohamed, Azali; Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi (Elsevier, 2001)
This paper presents an empirical analysis of panel unit root and panel cointegration tests of long-run absolute purchasing power parity (PPP) for seven Asian developing economies (ADE). The evidence shows that the panel parametric and non-parametric tests either with a trend term or without a trend term support the hypothesis of cointegration between the bilateral exchange rates and relative prices against the selected foreign country — Japan.